Intracranial Volumes of Healthy Children in the First 3 Years of Life: An Analysis of 270 Magnetic Resonance Imaging Scans. Issue 1 (17th May 2022) - Brandel, Michael G.; Kamel, George N.; Carbulido, Kristine; Belza, Caitlyn; Modi, Rishi; McKee, Ryan; Cronin, Brendan J.; Ewing, Emily; Lance, Samuel H.; Gosman, Amanda A.
Abstract : Background: There is a paucity of data on normal intracranial volumes for healthy children during the first few years of life, when cranial growth velocity is greatest. The aim of this study was to generate a normative predictive model of intracranial volumes based on brain magnetic resonance imaging from a large sample of healthy children to serve as a reference tool for future studies on craniosynostosis. Methods: Structural magnetic resonance imaging data for healthy children up to 3 years of age was acquired from the National Institutes of Health Pediatric MRI Data Repository. Intracranial volumes were calculated using T1-weighted scans with FreeSurfer (version 6.0.0). Mean intracranial volumes were calculated and best-fit logarithmic curves were generated. Results were compared to previously published intracranial volume curves. Results: Two-hundred seventy magnetic resonance imaging scans were available: 118 were collected in the first year of life, 97 were collected between years 1 and 2, and 55 were collected between years 2 and 3. A best-fit logarithmic growth curve was generated for male and female patients. The authors' regression models showed that male patients had significantly greater intracranial volumes than female patients after 1 month of age. Predicted intracranial volumes were also greater in male and female patients in the first 6 months of life as compared to previously published intracranial volume curves. Conclusions: To the authors' knowledge, this is the largest series of demographically representative magnetic resonance imaging–based intracranial volumes for children aged 3 years and younger. The model generated in this study can be used by investigators as a reference for evaluating craniosynostosis patients.